Roadkill and new records for giant armadillo (Priodontes maximus) in Central-Western Brazil - Hannibal, Wellington (2018)
Despite the widespread distribution of the giant armadillo Priodontes maximus, this species isfound at low densities, often in disrupted populations. Here we report 12 new records, including five incidentsof roadkill of P. maximus in different points of the Cerrado and one in an Atlantic Forest fragment in centralwesternBrazil. In addition to the relevant records, we discuss the negative effects of roadkills, which is a seriousissue for the conservation and maintenance of local populations of giant armadillo.